(3JWHjb TGed ddMReI (BSPSSs - (3MSjf Ydj(B, (3fLjHs ((3YeGf(B:s (3efThQGJ GdGgdjI(B,s, 2006)
(3jVe eaghe hWHjYI fXGe (Bspss(3, JgjFI edaGJ GdGONGd ddMReI (Bspss(3, GSJNOGe GhGeQ GdbGFeI (Bview(3, JfXje hJQJjH GdHjGfGJ HGSJNOGe GdbGFeI (Bdata(3, JMhjd GdHjGfGJ ef NdGd GdbGFeI (Btransformation (3GdGMUGA GdhUaj, (Bescriptive stastics(3, JMdjd hGSJcTGa GdHjGfGJ HGSJNOGe GdGeQ (BExplore(3, GNJHGQ (B(shi-square (x2 (3ef LOGhd GdJbGWY, (Bcrosstabs (3, GNJHGQ GdYjfGJ GdGMUGFjI HGSJNOGe (BT-test (3JMdjd GdJHGjf (BAnalysis variance (Anova) (3, JMdjd GdGQJHGW (Bcorrelation Analysis (3, JMdjd GdGfMOGQ (Bregression Analysis(3, GdGNJHGQGJ GddGeYdejI (Bnon-parametric tests(3, GdJMdjd GdYGedj (BFactor Analysis (3, JMdjd GdJeGjR (Bdes criminale Analysiss
(3HHdjhZQGajG(B: (3U(B.453-455s
Keywords: (3GdGMUGA GdJMdjdjs; (3GdGMUGA GdhUajs; (3GdHjGfGJ,GMUGAs